2005
DOI: 10.1038/sj.eye.6701964
|View full text |Cite
|
Sign up to set email alerts
|

External factors in the development of cataract

Abstract: Aims To provide an update on the risk factors for cataract development. Methods Review of the literature. Results Age and heredity are the most important risk factors associated with the different types of cataract. While the hereditary component is self-explanatory, increasing age serves as a surrogate for a number of potential external risk factors, the effect of which is cumulative. Identification of the risk factors that have a causal effect on cataract development may provide means for cataract prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 76 publications
(88 reference statements)
6
117
0
2
Order By: Relevance
“…Its pathology has multiple contributing factors, including exposure to UV light, tobacco, and certain specific chemicals; however, the effect is generally the sameaggregation of the eye lens crystallins (5,13,16,17,60,61). In line with the multiple causality of the disease, several distinct biochemical perturbations in vitro have been shown to cause crystallin aggregation (54,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 94%
“…Its pathology has multiple contributing factors, including exposure to UV light, tobacco, and certain specific chemicals; however, the effect is generally the sameaggregation of the eye lens crystallins (5,13,16,17,60,61). In line with the multiple causality of the disease, several distinct biochemical perturbations in vitro have been shown to cause crystallin aggregation (54,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 94%
“…Lifetime exposure to chronic UVR has been directly associated with the development of cortical cataracts in man, and the World Health Organization has reported that as much as 20% of cataract-associated blindness may be due to UVR exposure. Genetic factors, diabetes, steroid use, and smoking are also strongly associated with cataract formation in humans (Robman and Taylor, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors for both cortical and PSC include diabetes and steroid use, while smoking increases the risks of nuclear and PSC (28). The risk of cortical cataract is also related to ultraviolet radiation (29). We collected information on these factors and all analyses were adjusted for age, with additional adjustment for gender and smoking where necessary (if there was indication of confounding).…”
Section: Mrena Et Almentioning
confidence: 99%